Pengaruh Dana Desa dan Pembangunan Infrastruktur Terhadap Indeks Desa Membangun di Kecamatan Barabai - Rezkia, Laras Sania; Yunani, Ahmad (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This study aimed to determine the effect of village funds and infrastructure development on the index of developing villages simultaneously and partially in the Barabai sub-district. The data used in this study is secondary data, namely data obtained based on available data and has been compiled by the Department of Community and Village Empowerment and Barabai District. The data analysis technique used in this research is panel data regression. The results of this study show that (1) simultaneously, Village Funds and Infrastructure Development have a significant effect on the Village Building Index, (2) Infrastructure Development is the most influential variable on the Village Building Index, but the effect is negative, and (3) steps to increase the index village development is to strengthen village deliberations and improve the development of empowerment and empowerment of rural communities based on the recommendation of the input result of the village index questionnaire in the previous year.